Accuracy of CRIB II Score in Predicting the Neonatal Mortality in very Preterm Babies - Abdul Rehman, Muhammad Haroon Hamid (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the accuracy of Clinical Risk Index for Babies (CRIB) II score to predict mortality in very preterm babies. Methodology: In this cross-sectional study at Neonatal Intensive Care Unit (NICU) of The Children’s Hospital, Lahore, 145 very preterm neonates admitted in NICU were enrolled. We determined gestational age, weight, rectal temperature and base excess for both genders within first hour of the admission. The collected data was entered on CRIB II score chart and risk of mortality was calculated. The babies were reviewed daily in NICU till final outcome (mortality or no mortality). Results: In this study, out of 145 patients, 47.59%(n=69) were females and 52.41%(n=76) were males. Mean+SD for gestational age, birth weight, rectal temperature, base excess and CRIB II score was 29.90+1.70 weeks, 1171.31±192.16 grams, 36.92+0.39 degrees Celsius, -3.63±6.63 and 5.03±3.04 respectively. Actual mortality rate was 36.55%(n=53) whereas 63.45%(n=92) had no mortality; Predicted mortality rate on CRIB II score was 41.38% (n=60) whereas 58.62%(n=85) had no mortality. Accuracy of CRIB II score to predict mortality in very preterm babies admitted in NICU of The Children’s Hospital, Lahore was 84.14%. It had sensitivity of 84.91%, specificity of 83.70%, (PPV) of 75.00% and (NPP) of 90.58 %. Area under the receiver operating characteristics (ROC) curve was 0.840 (std. error=0.035; p-value=0.000). Conclusion: We concluded that CRIB II score is a valid clinical score with higher accuracy to predict neonatal mortality in very preterm babies.